Paul Kagame na crise entre Burundi e Ruanda ou o domínio do Heartland Africano em causa? - Almeida, E. C. (Figuras & Negócios, 2024)
Abstract: The (somewhat recent) crisis between Burundi and Rwanda (Wendy, 2024) brings once again to the fore a problem that has its roots in German-Belgian colonization and its main breaking point with the Second Congo War. Alongside this mentioned colonial issue, there is a figure who stands out as one of the most significant personalities, albeit not for the best reasons, in the latent crisis between Burundians and Rwandans in this particular case, as well as in the precarious situation in the Great Lakes Region, that is, in the great African Heartland (Mackinder, 1996 & Almeida, 2022). This text attempts to synthesize this period to better understand the anthropological, historical, and political intricacies underlying this more recent crisis between the two former territories of the Kingdom of Urundi; and to provide an overview of the current situation and how Kagame has been delaying maneuvers for peace in the region.